2000
DOI: 10.4054/demres.2000.3.1
|View full text |Cite
|
Sign up to set email alerts
|

Old-Age Mortality in Germany prior to and after Reunification

Abstract: Recent trends in German life expectancy show a considerable increase. Most of this increase has resulted from decreasing mortality at older ages. Patterns of oldest old mortality (ages 80+) differed significantly between men and women as well as between East and West Germany. While West German oldest old mortality decreased since the mid 1970s, comparable decreases in East Germany did not become evident until the late 1980s. Yet, the East German mortality decline accelerated after German reunification in 1990,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 17 publications
1
37
0
3
Order By: Relevance
“…Studies from South Africa (Case 2004) and Mexico (Aguila, Kapteyn, and Smith 2015) also suggest that these transfers could help to protect the health and survival of older eastern Germans. As the health of elderly people in eastern Germany has improved markedly since reunification (Vogt and Kluge 2013;Klenk et al 2007;Gjonça, Brockmann, and Maier 2000), it is possible that they benefited from this protective effect. Our descriptive study cannot answer this question, but our results may serve as a first step toward addressing this relationship analytically.…”
Section: Discussionmentioning
confidence: 99%
“…Studies from South Africa (Case 2004) and Mexico (Aguila, Kapteyn, and Smith 2015) also suggest that these transfers could help to protect the health and survival of older eastern Germans. As the health of elderly people in eastern Germany has improved markedly since reunification (Vogt and Kluge 2013;Klenk et al 2007;Gjonça, Brockmann, and Maier 2000), it is possible that they benefited from this protective effect. Our descriptive study cannot answer this question, but our results may serve as a first step toward addressing this relationship analytically.…”
Section: Discussionmentioning
confidence: 99%
“…Also Shkolnikov et al (2007) found in their study of the German pensioners that socioeconomic mortality differentials for the year 2003 were similar in both parts of Germany. In fact, as Luy (2004) and Gjonca et al (2000) discussed in their works, it is the differences in medical care, particularly in nursing, which influenced mortality levels in the two states. Mortality in East Germany was higher before reunification, but caught up to the western standard shortly thereafter.…”
Section: Discussionmentioning
confidence: 99%
“…Caselli and Egidi, 1980;Bourgois-Pichat, 1985;Marmot, 1996a, 1996b;Hertzman et al, 1996;Meslé and Hertrich, 1997;Vallin and Meslé, 2001;Meslé and Vallin, 2002). Figure 1 shows that the widening of the life expectancy gap was caused by the fact that East German life expectancy at birth increased at a lower pace for both sexes, whereas life expectancy in West Germany rose more rapidly (Höhn and Pollard, 1991;Scholz, 1996;Gjonça et al, 2000;Nolte et al 2000a). The differences peaked in 1988 for women (almost 3 years) and in 1990 for men (roughly 3.5 years).…”
Section: Why Life Expectancy Differences Between Western and Eastern mentioning
confidence: 99%
“…The German experience thus is used to understand the reasons behind recent mortality changes. The two pre-war German regions were characterized by a demographic composition and behavior that was almost identical until 1945, followed however by 45 years under different political and socioeconomic structures and resulting in demographic developments that were entirely different (Dinkel, 1992(Dinkel, , 1994(Dinkel, , 1999Gjonça et al, 2000). With unification in 1990, East Germany adopted the western societal and economic system, causing sudden changes in all of its demographic processes.…”
Section: Why Life Expectancy Differences Between Western and Eastern mentioning
confidence: 99%
See 1 more Smart Citation